The Role of Endowments in Financial Markets: Key Trends in 1990-2020 in the USA (on the example of the US education sector) - K. B. Bakhtaraeva (Мир новой экономики, 2021)
This article describes the key trends in the development of endowments as institutional investors using the example of US educational endowments in 1990-2020. The paper also gives an overview of the world structure of endowments assets by regions and sectors. Although much research has been done on investment behaviour and return of endowments, there are not so many works analysing the long-term trends in the development of endowments. The study uses methods of systemic and comparative analysis and statistical methods. The article demonstrates an intensive growth of endowment assets during 1990-2000 and the following maturing market. Special attention is given to identifying and analysing changes in the structure and concentration levels of the endowment's market. The author suggests that the earlier model of many different-sized funds has changed to the model where significant funds dominate and concentrate most assets. The paper also explains the changes in the investment behaviour of endowments, including how the size of endowment influences the asset structure of funds' investment portfolios and return. The paper shows the growing role of state universities endowments, an increase in the regulatory burden. Also, it presents some forecast of key trends in the development of endowments in the long run.